KOLABORASI PERSONIL SEKOLAH DALAM MENGATASI PERILAKU BULLYING ( DI SMA NEGERI 2 LUBUK SIKAPING ) - Muthia Indah Pratiwi; Rici Kardo; Rahma Wira Nita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the limited collaboration between guidance and counseling (GC) teachers and subject teachers in addressing student bullying behavior. The objectives of this study are to describe the collaboration between GC teachers and subject teachers in overcoming student bullying behavior, reviewed from: 1) the forms of collaboration, 2) the challenges of collaboration, and 3) the effects of collaboration. This study used a qualitative approach with descriptive data. Key informants in this study were a GC teacher (IAH) and a subject teacher (RP), along with three additional informants: a homeroom teacher, the vice principal for student affairs, and students. Data collection techniques were conducted through interviews, observation, and documentation studies, while data analysis techniques used the stages of data reduction, data presentation, and conclusion drawing. The results show that 1) the forms of collaboration established between GC teachers and subject teachers are carried out through information exchange about students, case discussions, and the fostering of positive behavior. 2) The challenges faced include differences in perspective, lack of communication, and time constraints. 3) The effects of this collaboration are very tangible and positive, especially in improving student discipline, honesty, and responsibility. Collaboration also impacts the improvement of teacher professionalism and the overall quality of the learning environment. Based on the research results, it is recommended that GC teachers and subject teachers actively improve communication and align perspectives through routine discussions, and utilize technology for efficient information exchange to strengthen collaboration in fostering positive behavior and addressing bullying behavior.